Establishing the protocols for the South Australian Emergency Department Admission Blood Psychoactive Testing (EDABPT) programme for drug surveillance. (13th March 2021) - Partridge, Emma; Alfred, Sam; Camilleri, Andrew; Green, Hannah; Haustead, Daniel; Kostakis, Chris; Mallon, Jake; Mason, Kerryn; Rivers‐Kennedy, April; Stockham, Peter
Abstract: Objective: ED presentations because of illicit use of psychotropic drugs and pharmaceuticals result in significant medical harm and resource consumption. Patient assessment is complicated by the regular emergence of new psychoactive substances, difficulties associated with their identification and a lack of information about their effects. Here we report the protocol for the Emergency Department Admission Blood Psychoactive Testing (EDABPT) programme, an observational study utilising clinical data capture and definitive drug identification to assess the medical impact and patterns of illicit drug use in the community, and their geographic and temporal fluctuations. The study provides data to an early warning system targeting an improved public health response to emerging drugs of concern. Methods: Enrolment of adult patients presenting with suspected illicit drug use occurs at four major EDs in a single urban setting. Clinical and demographic data are collected by treating clinicians. Blood samples are collected at presentation and frozen on site prior to transport to a specialised forensic facility for comprehensive toxicological screening. Results: Results are fed back to clinicians and disseminated more broadly via an existing local early warning system. Targeted warnings and public health releases are instigated where heightened risk or harm is identified. Conclusion: The study pairs city‐wide patient enrolment with analytically confirmed toxicology results to allow broad sampling and identification of illicit drugs causing medical harm. It provides a mechanism for the identification of new agents as they emerge in the community, delivers a relevant and reliable source of information for public health agencies and clinicians and supplements existing local early warning mechanisms. Abstract : The South Australian Emergency Department Admission Blood Psychoactive Testing (EDABPT) study utilises clinical data capture and definitive drug identification to assess the medical impact and patterns of illicit drug use in the community. It provides a mechanism for the identification of new agents as they emerge in the community, delivers a relevant and reliable source of information for public health agencies and clinicians and supplements existing local early warning mechanisms.